Revisiting Dead Poets Society as a Tool for Studying Applications of Power. (June 2022) - Holbrook, Robert L.; Stoner, Jason
In organizational behavior, management, and leadership courses, the topic of power is often a focal point. However, as with many theories and concepts, students sometimes struggle to see the management and leadership applications until examples are used to highlight the theories and concepts in practice. In this article, we outline how a classic 1980s American film can be used as a teaching tool for both physical (in-person) and online courses to help students see the application of power concepts. A variety of resources are provided to help instructors incorporate the film into their classes.